Effects of quercetin on exercise performance, physical activity and blood supply in a novel model of sustained hind-limb ischaemia. Issue 1 (11th February 2021) - Phie, J; Krishna, S M; Kinobe, R; Moxon, J V; Andrade-Lima, A; Morton, S K; Lazzaroni, S M; Huynh, P; Golledge, J
Abstract: Background: There are currently few effective drugs to treat the leg symptoms of peripheral arterial disease (PAD). Previous studies have suggested that the nutraceutical, quercetin, can improve exercise performance and reduce pain sensitivity in healthy mice and improve blood supply in a rodent model of acute hind-limb ischaemia. These models may not be relevant to people with PAD. The aim of this study was to examine the effect of quercetin on exercise performance, physical activity and blood supply in a novel mouse model of sustained hind-limb ischaemia. Methods: Hind-limb ischaemia was induced in 6-month-old male apolipoprotein E-deficient mice using a novel two-stage surgical procedure. Five days after induction of ischaemia, mice were allocated to commence dietary quercetin or a control diet for 4 weeks. The primary outcome was exercise performance evaluated using a treadmill test. Other outcomes included physical activity, estimated by an open field test, and hind-limb blood supply, assessed by laser Doppler monitoring. Results: A sustained reduction in relative limb blood supply ( P  <   0.001) was achieved consistently in all 48 mice before allocation to a control ( n  = 24) or quercetin ( n  = 24) diet. Quercetin did not improve exercise performance ( P  =   0.785), physical activity ( P  =   0.151) or relative limb blood supply ( P  =   0.954) over the 4-week assessment period. Conclusion: These data suggest that quercetin does not improve exercise performance, physical activity or limb blood supply in mice with sustained hind-limb ischaemia, and therefore is unlikely be an effective treatment for PAD. Abstract : The dietary flavonoid quercetin has been reported to improve exercise performance in healthy mice and people, and increase limb perfusion in models of acute hind limb ischemia. Acute hind limb ischemia models may not be representative of human peripheral artery disease.We report that quercetin does not improve exercise performance or limb perfusion in a newly developed two stage mouse model of sustained hind limb ischemia. Our findings suggest that quercetin may not be beneficial for patients with sustained limb ischemia due to peripheral artery disease. little evidence of efficacy